The impact of electrostatic interactions on ultrafast charge transfer at Ag29 nanoclusters–fullerene and CdTe quantum dots–fullerene interfaces. Issue 14 (23rd November 2015) - Ahmed, Ghada H.; Parida, Manas R.; Tosato, Alberto; AbdulHalim, Lina G.; Usman, Anwar; Alsulami, Qana A.; Murali, Banavoth; Alarousu, Erkki; Bakr, Osman M.; Mohammed, Omar F.
Abstract : We report how electrostatic interactions significantly impact charge transfer at CdTe QDs/fullerene interfaces. Abstract : A profound understanding of charge transfer (CT) at semiconductor quantum dots (QDs) and nanoclusters (NCs) interfaces is extremely important to optimize the energy conversion efficiency in QDs and NCs-based solar cell devices. Here, we report on the ground- and excited-state interactions at the interface of two different bimolecular non-covalent donor–acceptor (D–A) systems using steady-state and femtosecond transient absorption (fs-TA) spectroscopy with broadband capabilities. We systematically investigate the electrostatic interactions between the positively charged fullerene derivative C60 -( N, N dimethylpyrrolidinium iodide) (CF) employed as an efficient molecular acceptor and two different donor molecules: Ag29 nanoclusters (NCs) and CdTe quantum dots (QDs). For comparison purposes, we also monitor the interaction of each donor molecule with the neutral fullerene derivative C60 -(malonic acid) n, which has minimal electrostatic interactions. Our steady-state and time-resolved data demonstrate that both QDs and NCs have strong interfacial electrostatic interactions and dramatic fluorescence quenching when the CF derivative is present. In other words, our results reveal that only CF can be in close molecular proximity with the QDs and NCs, allowing ultrafast photoinduced CT to occur. It turned out that the intermolecular distances, electronic coupling and subsequently CT from the excited QDs or NCs to fullerene derivatives can be controlled by the interfacial electrostatic interactions. Our findings highlight some of the key variable components for optimizing CT at QDs and NCs interfaces, which can also be applied to other D–A systems that rely on interfacial CT.